Whole genome sequence of an Escherichia coli ST410 isolate co-harbouring blaNDM-5, blaOXA-1, blaCTX-M-15, blaCMY-2, aac(3)-IIa and aac(6')-Ib-cr genes isolated from a patient with bloodstream infection in China. (December 2019) - Huang, Junwei; Ma, Shanshan; Yu, Qian; Fu, Miao; Shao, Lingli; Shan, Xiaoyun; Li, Xi
Abstract: Objectives: Mortality associated with carbapenemase-producing Enterobacteriaceae is high as there are few therapeutic options. Escherichia coli sequence type 410 (ST410) is currently an international high-risk clone and is responsible for a large number of clinical infections. Here we report the draft genome sequence of a ST410 clinical E. coli isolate (ECS9) co-harbouring bla NDM-5, bla OXA-1, bla CTX-M-15, bla CMY-2, aac(3)-IIa and aac(6')-Ib -cr genes, obtained from a patient with bloodstream infection in China. Methods: The genome of E. coli ECS9 was sequenced using an Illumina HiSeq TM 4000 instrument with a 150-bp paired-end approach. Generated sequence reads were assembled using Velvet 1.2.10. Contigs were annotated using Rapid Annotation using Subsystem Technology (RAST), and further whole-genome sequence data analyses were performed. Results: Escherichia coli ECS9 belongs to multilocus sequence typing (MLST) ST410. The total number of assembled bases was 4 935 145 bp, with 5077 protein-coding sequences. The presence of the bla NDM-5, bla OXA-1, bla CTX-M-15 and bla CMY-2 genes was detected in addition to other antimicrobial resistance genes conferring resistance to fluoroquinolones, aminoglycosides, trimethoprim, sulfonamides and tetracyclines. Conclusion: To our knowledge, this is the first report of an E. coli ST410 strain co-harbouring bla NDM-5, bla OXA-1, bla CTX-M-15, bla CMY-2, aac(3)-IIa and aac(6')-Ib -cr, obtained from a bloodstream infection in China. The presented genome sequence of carbapenemase-producing E. coli strain ST410 could provide further insight into the acquisition of multiple resistance genes by this successful lineage.